2012
DOI: 10.1155/2012/964064
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effect of Control Flow on the Unit Testing Effort of Classes: An Empirical Analysis

Abstract: The aim of this paper is to evaluate empirically the relationship between a new metric (Quality Assurance Indicator-Qi) and testability of classes in object-oriented systems. The Qi metric captures the distribution of the control flow in a system. We addressed testability from the perspective of unit testing effort. We collected data from five open source Java software systems for which JUnit test cases exist. To capture the testing effort of classes, we used different metrics to quantify the corresponding JUn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
5
2
1

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(10 citation statements)
references
References 42 publications
(83 reference statements)
0
10
0
Order By: Relevance
“…In [15], Badri et al investigated the capability of lack of cohesion metrics to predict testability using logistic regression methods. More recently, Badri et al [16,47] investigate the effect of control flow of the unit testing effort of classes.…”
Section: Software Testabilitymentioning
confidence: 99%
“…In [15], Badri et al investigated the capability of lack of cohesion metrics to predict testability using logistic regression methods. More recently, Badri et al [16,47] investigate the effect of control flow of the unit testing effort of classes.…”
Section: Software Testabilitymentioning
confidence: 99%
“…The results indicated that complexity, size, cohesion, and (to some extent) coupling were found to be significant predictors of the testing effort of classes. Later, Badri et al [18], [19] studied the effect of control flow of the unit testing effort of classes. They classified the classes into low and high according to the required testing effort.…”
Section: Related Workmentioning
confidence: 99%
“…For more details see [12], [22], [23]. The Qi metric is based on Control Call Graphs (CCG), which are a reduced form of traditional Control Flow Graphs (CFG).…”
Section: Quality Assurance Indicatormentioning
confidence: 99%
“…Testability was measured (inversely) by the number of lines of test code (JUnit test suites) and the number of assert statements in the test code. More recently, we investigated the capacity of the Qi metric in predicting the unit testing effort of classes using regression analysis techniques [23].…”
mentioning
confidence: 99%